Activities and characteristics of a manager in the function of improving the strategic activity of a company - Cvjetković Milovan; Cvjetković Milena; Jovanović Zoran; Kalinić Marija (Oditor, 2021)
The paper deals with the analysis of the role of activities and characteristics of the manager as a factor in improving the strategic activity of a company. The survey included 327 managers of different levels who are employed in companies operating on the territory of the Republic of Serbia. Correlation analysis confirmed statistically significant relationships between observed activity variables and managerial characteristics and strategic action variables. The regression method confirmed that the variables communication and innovation and flexibility had the greatest influence on all analyzed variables of strategic action, while the variables of activity and characteristics of managers had the greatest importance on the variables of strategic decision making and quality of vision and mission. The aim of the presented research is to point out the importance of activities and characteristics of managers with the goal of business promotion, primarily through strategic action, and that they can be crucial for improving the market and competitive position of companies.